Microbiological evaluation of feet-cutter disc for broiler with a self-washing system using heated and non-heated water - Cavani, Ricardo [UNESP]; Rubio, Marcela Da Silva [UNESP]; Alves, Lucas Bocchini Rodrigues [UNESP]; Alves, Khauston Augusto Pereira; Cardozo, Marita Vedovelli (Instituto de Tecnologia de Alimentos - ITAL, 2023)
The increased worldwide demand for chicken meat requires constant automation of operating systems and the proper implementation of self-control programs by slaughterhouses. Thus, this study aimed to evaluate the efficacy of a self-washing system using heated water on reducing the load of public health concern bacteria on a broiler feet-cutter disc. In a three-month period, 84 samples (n = 42 per group) were collected for microbiological analysis from the feet-cutter disc with an operational self-washing process with Non-Heated Water (NHW) and Heated Water (HW). The logarithmic counts of Mesophilic Aerobics, Sulphite-Reducing Clostridia (SRC), Escherichia coli and Staphylococcus aureus in the NHW group were 1.82, 0.56, 0.31 and 0.14 Log10 CFU/cm2, respectively, whereas in the HW group were 1.17, 0.04, 0.15 and 0.08 Log10 CFU/cm2. Salmonella spp. was absent in all evaluated samples in both groups. The heated-water system reduced bacterial count, but statistical differences were solely observed for Mesophilic Aerobics and SRC. Nevertheless, its usage could be an additive in the operational procedure to avoid microbiological violations of food safety, in addition to being easy-to-implement and affordable for the industry.

Heating Water (HW) for self-washing systems in feet-cutter discs is easy-to-implement for the industryBacterial load can be reduced by heated-water on a feet-cutter disc surfaceA self-washing system could be used in self-control programs, to avoid violation of food safety

O aumento mundial da demanda por carne de frango exige constante automação de sistemas de operação e implementação adequada de programas de autocontrole pelos abatedouros. Assim, o objetivo do presente estudo foi avaliar a eficiência de sistema de autolavagem com água aquecida na redução da contagem de bactérias de interesse em saúde pública em disco corta-pés de frangos. Em um período de três meses, 84 amostras (n = 42, por grupo) foram colhidas para análises microbiológicas em disco corta-pés contando com um sistema operacional de autolavagem com água não aquecida (NHW) e água aquecida (HW). As contagens de Aeróbios Mesófilos, Clostridium Sulfito-redutor, Escherichia coli e Staphylococcus aureus, no grupo NHW, foram de 1,82, 0,56, 0,31 e 0,14 Log10 UFC/cm2, respectivamente, enquanto que, no grupo HW, foram de 1,17, 0,04, 0,15 e 0,08 Log10 UFC/cm2. Salmonella spp. foi ausente em todas amostras avaliadas, em ambos os grupos. O sistema com água aquecida reduziu as contagens bacterianas, mas diferenças estatísticas foram observadas somente em Aeróbios Mesófilos e Clostridium Sulfito-redutor. Apesar disso, seu uso pode ser um adicional ao procedimento operacional para evitar a violação dos limites microbiológicos de segurança alimentar, além de ser um sistema de fácil implementação e de baixo custo.
Avaliação microbiológica de disco corta-pés de frangos com sistema de autolavagem utilizando água aquecida e não aquecida
Keywords: Cross-contamination; Hock; Poultry; Saw blade; Self-control program; Water jet; Aves domésticas; Contaminação cruzada; Disco de serra; Jato de água; Jarrete; Programa de autocontrole